The Effect of Job Training & Work Environment on Employee Performance at Crowne Plaza Residences Jakarta - Djunaid, Ika Suryono (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2023)
Job training and work environment are one of the factors that are quite important in improving employee performance in a company. In this study, researchers conducted research with the aim of knowing the effect of job training on employee performance at Crowne Plaza Jakarta Residences and the effect of the work environment on employee performance at Crowne Plaza Jakarta Residences. This type of research used is descriptive with quantitative methods and the writing method that researchers use is a questionnaire with a saturated sample technique with employee respondents at Crowne Plaza Jakarta Residences, interviews and literature review. The sample in this study with a sample of 32 respondents. The results of this study support the hypothesis made, namely job training and work environment have a positive influence on employee performance. Suggestions that can be given to Crowne Plaza Jakarta Residneces are to maintain and improve the job training and work environment that has been carried out.